Growth and mortality rate of the Napan-Yaur Coral Trout, Plectropomus leopardus (Pisces: Serranidae), Cenderawasih Bay National Park, Indonesia - RONI BAWOLE; MUDJI RAHAYU; UNSTAIN N.W.J. REMBET; ARNOLDUS S. ANANTA; FERAWATI RUNTUBOI; RIDWAN SALA (Biodiversitas Journal of Biological Diversity, 2017)
Bawole R, Rahayu M, Rembet UNWJ, Ananta AS, Runtuboi F, Sala R. 2017. Growth and mortality rate of the Napan-Yaur Coral Trout, Plectropomus leopardus (Pisces: Serranidae), Cenderawasih Bay National Park, Indonesia. Biodiversitas 18: 758-764. Coral trout, Plectropomus leopardus, is one of the important fishery resources in Cenderawasih Bay National Park, Papua, Indonesia. The catch production of this species has declined since 2015. This study aims to assess growth, mortality, and exploitation rate parameters of P. leopardus taken from Napan Yaur water, Cenderawasih Bay National Park (CBNP), Indonesia. The data were collected during periods of February to March 2016. Growth and mortality parameters were analyzed using von Bertalanffy method. Some fish samples used in this study was 123 individuals, with the average length of 32.34 Â± 5.13 cm, the maximum length of 48.00 cm and minimum length of 24.5 cm. The von Bertalanffy analysis showed that the growth coefficient (K) was 0.34 year-1, Lâˆž was 47.78 cm and t0 was-0.09 year-1. The estimation of total mortality (Z) was 1.61 year-1, natural mortality (M) was 0,75year-1 for fishing mortality (F) was 0.86 year-1, and exploitation rate (E) was 0.53 year-1. The results indicated that most P. leopardus caught were at the pre-maturity size (age) and have been exploited at slightly above its optimum exploitation level. Nevertheless, P. leopardus is categorized as fast growing and long-lived fish species. These findings are important to fisheries management and conservation authorities to fish exploitation in the future.